Techno-economic and environmental assessment of CO2 utilisation processes for the production of dimethyl ether and olefins - Ahmed, Mohamed (2023)
Decarbonising heavy industry, such as cement manufacturing, is now seen as essential to meet the climate change target of limiting global warming to 2°C since pre-industrial times. To achieve deep decarbonisation, carbon capture and storage (CCS) is required and, in areas where there is no storage capacity close by, the conversion of CO2 to added-value products, like dimethyl ether (DME) and olefins, needs to be considered. In this study, the techno-economic performance and environmental impacts of carbon dioxide utilisation (CCU) systems are evaluated for indirect DME synthesis and methanol to olefins (MTO) using three alternative reforming routes: dry methane reforming, bireforming and tri-reforming. The CO2 source is a cement manufacturing plant equipped with an oxyfuel CO2 capture unit. The process scenarios are simulated in Aspen Plus V12 and integrated with MATLAB R2020b to allow for optimisation towards either minimising production costs or minimising environmental impact. The optimisation was completed using a simulated annealing hybrid function with pattern search and a genetic algorithm complete search. The CO2 utilisation scenarios showed global warming potentials (GWP) ranging from 3.35 to 4.76 tCO2-eq∙t -1 DME and 2.74 to 4.19 tCO2-eq∙t-1 olefins; which is 16.34 - 41.12% and 7.51 - 86.48% lower than the conventional steam reforming process, respectively. The total production cost for the CCU scenarios ranged from $819.32 to $970.87 t-1 DME and $1189.03 to $1540.48 t-1 olefins; which is 3.24 - 22% and 11.03-43.85% higher than the conventional production process, respectively. For the MTO CCU scenarios this translates to a net loss of -$749.65 to -$362.97 t -1 olefins. Applying heat integration further reduced the GWP for the CCU scenarios to 2.2 – 3.27 tCO2 -eq ∙t -1 DME and 0.26 - 1.75 tCO2-eq∙t-1 olefins, where ADTRI-GWP displayed the lowest GWP for both the DME and MTO scenarios. This was 10.7 - 64.55% and 7.51 - 86.48% lower than the conventional steam reforming process, respectively. The total production cost was reduced to $482.98 to 683.52 t-1 DME and $857.87 to $1083.06 t-1 olefins; whilst the total production cost of the conventional production process’ decreased to $417.78 t-1 DME and $578.46 t-1 olefins. For the CCU-based scenarios, BI-OPEX displayed the lowest total production cost for both the DME and MTO scenarios. In the case of MTO production, the net profit or loss for the CCU-based scenarios and the conventional production scenario ranged from - $288.64 to $100.85 t-1 olefins and $230.45 t-1 olefins, respectively. This was a significant improvement from the equivalent scenarios without heat integration. The cost of global warming potential reduction (CGWP) was introduced to determine the link between the difference in production cost and the GWP of CCU and conventional processes. The CGWP ranged from $93.69 to $581.23 and $156.12 to $2800.23 per tCO2-eq for the DME CCU scenarios and MTO CCU scenarios, respectively. In both cases the production process using bireforming technology displayed the lowest CGWP. The effect of applying a carbon levy on natural gas (NG) used in the conventional production method was studied. For the CCU scenarios to achieve an equitable production cost to the conventional production method, a carbon levy of $94.49 to $385.13 t-1 NG and $160.71 to $655.32 t -1 NG is required for the DME CCU scenarios and MTO CCU scenarios, respectively. Overall, the results of this study indicate CCU processes utilising bi-reforming provided the highest commercial feasibility when compared to dry and tri-reforming technologies for the production of olefins and DME, whilst providing significant GWP reduction. It was also found that in order to minimise GWP, the use of adiabatic tri-reforming technology is preferred.